Can cryptos hedge against inflation? Evidence from biwavelet analysis - Thai Hong Le; Duc Anh Nguyen; Dung Anh Le (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
This paper aims to explore the role of cryptocurrencies as an effective hedging tool against inflation across different investment horizons. Specifically, we investigate the co-movement between the Consumer Price Index (CPI) in the US, Euro, and Japan, and the returns as well as volatilities of four key cryptocurrencies (Bitcoin, Ethereum, Litecoin, and Ripple). In doing so, we adopt the biwavelet coherence framework using monthly data spanning over the period from September 2015 to May 2023. Our results suggest that cryptocurrencies, except Ethereum, can serve as safe-haven and effective long-term hedging assets against inflation in the US and EU. On the other hand, Litecoin stands out as the only crypto that can effectively hedge assets in the medium term. In Japan, we observe significantly low to no co-movement between cryptocurrencies’ returns and the CPI, suggesting the usefulness of the sampled cryptocurrencies as diversifiers against inflation. Our findings thus have implications for not only investors seeking to diversify their portfolios and mitigate inflation risk but also policymakers navigating the evolving landscape of digital assets and inflation management strategies.